2014
DOI: 10.1007/s40477-014-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Acquired unilateral pulmonary vein atresia in a 3-year-old boy

Abstract: While unilateral pulmonary venous atresia (UPVA) most commonly presents as an extremely rare late embryological defect resulting in complete occlusion or absence of the PV pathway, it may also be an acquired pathology. We present a 3-year-old boy who presented with mild respiratory distress. Neonatal echocardiographic investigations revealed normal mediastinal anatomy and pulmonary vasculature with a bicuspid aortic valve. However, follow-up Doppler investigation revealed a pulmonary artery size difference wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Overall, the prognosis of unilateral PVA was still guarded, with an approximately 50% mortality rates in untreated patients, [ 11 ] so early and accurate diagnosis is quite pivotal and essential before pulmonary hypertension or massive pulmonary hemorrhage occurred. Being aware of the possibility of unilateral PVA and avoidance of misdiagnosis of idiopathic pulmonary hemosiderosis when confronted with childhood patients presenting with hemoptysis, is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prognosis of unilateral PVA was still guarded, with an approximately 50% mortality rates in untreated patients, [ 11 ] so early and accurate diagnosis is quite pivotal and essential before pulmonary hypertension or massive pulmonary hemorrhage occurred. Being aware of the possibility of unilateral PVA and avoidance of misdiagnosis of idiopathic pulmonary hemosiderosis when confronted with childhood patients presenting with hemoptysis, is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…However, some scholars believe that UPVA is a secondary vascular occlusion change, and the causes of secondary UPVA include postoperative complications of congenital heart disease [5] , mediastinal tumor, pericardial or mediastinal infection, cardiac tumor, and thrombosis. Mohammed Firdouse et al [6] reported a case where a child had a normal pulmonary artery and pulmonary vein before examination, but UPVA was found during follow-up. The patient had not undergone surgery because there were no obvious clinical manifestations.…”
Section: Etiologymentioning
confidence: 99%